HUBUNGAN KEKUATAN OTOT LENGAN DAN KOORDINASI MATA-TANGAN DENGAN KEMAMPUAN SHOOTING PERMAINAN BOLA BASKET PADA SISWA EKSTRAKURIKULER SMA NEGERI 1 UJUNG BATU - Saputro, Andre; Manurizal, Lolia; Sinurat, Ridwan (Journal Of Sport Education and Training, 2020)
This study aims to determine the relationship between arm muscle strength and shooting ability, to determine the relationship between eye-hand coordination and shooting ability, to determine the relationship between arm muscle strength and eye-hand coordination simultaneously with shooting ability in basketball game for extracurricular students at SMA Negeri 1 Ujung Batu. This type of research is quantitative research, the method used is correlation. Data collection uses tests and measurements of eye-hand coordination and arm muscle strength and shooting. The design used in this study is a correlational design, which is to find whether there is a relationship between the independent variable and the dependent variable and how close the relationship is as well as the meaning or not of the relationship. then the sample in this study only 15 people who were taken male sex with a purposive sampling method of sampling. Based on the research results obtained r count = 0.258> r (0.05) (15) = 0.514 it can be concluded that there is no significant relationship between arm muscle strength and shooting ability of extracurricular basketball students at SMA Negeri 1 Ujung Batu ". Obtained rhitung = -0.112> r (0.05) (15) = 0.514 it can be concluded that there is no significant relationship between eye-hand coordination with the shooting ability of basketball extracurricular students at SMA Negeri 1 Ujung Batu ". Obtained r count = 0.272> r (0.05) (15) = 0.514 it can be concluded that there is no correlation between arm muscle strength and eye-hand coordination with the shooting ability of basketball extracurricular students at SMA Negeri 1 Ujung Batu. In conclusion there is no relationship between arm muscle strength and eye-hand coordination with the shooting abilities of basketball extracurricular students at SMA Negeri 1 Ujung Batu.